Comparison of the SAWNUC model with CLOUD measurements of sulphuric acid‐water nucleation. Issue 20 (27th October 2016) - Ehrhart, Sebastian; Ickes, Luisa; Almeida, Joao; Amorim, Antonio; Barmet, Peter; Bianchi, Federico; Dommen, Josef; Dunne, Eimear M.; Duplissy, Jonathan; Franchin, Alessandro; Kangasluoma, Juha; Kirkby, Jasper; et al.
Abstract: Binary nucleation of sulphuric acid‐water particles is expected to be an important process in the free troposphere at low temperatures. SAWNUC (Sulphuric Acid Water Nucleation) is a model of binary nucleation that is based on laboratory measurements of the binding energies of sulphuric acid and water in charged and neutral clusters. Predictions of SAWNUC are compared for the first time comprehensively with experimental binary nucleation data from the CLOUD chamber at European Organization for Nuclear Research. The experimental measurements span a temperature range of 208–292 K, sulphuric acid concentrations from 1·10 6 to 1·10 9 cm −3, and distinguish between ion‐induced and neutral nucleation. Good agreement, within a factor of 5, is found between the experimental and modeled formation rates for ion‐induced nucleation at 278 K and below and for neutral nucleation at 208 and 223 K. Differences at warm temperatures are attributed to ammonia contamination which was indicated by the presence of ammonia‐sulphuric acid clusters, detected by an Atmospheric Pressure Interface Time of Flight (APi‐TOF) mass spectrometer. APi‐TOF measurements of the sulphuric acid ion cluster distributions ( ( H 2 SO 4 ) i · HSO 4 − with i = 0, 1, ..., 10) show qualitative agreement with the SAWNUC ion cluster distributions. Remaining differences between the measured and modeled distributions are most likely due to fragmentation in the APi‐TOF. The CLOUD results are in good agreement with previously measured cluster binding energies and show the SAWNUC model to be a good representation of ion‐induced and neutral binary nucleation of sulphuric acid‐water clusters in the middle and upper troposphere. Key Points: Particle formation rates from SAWNUC model and CLOUD measurements at 208‐248 K generally agree Comparison of formation rates at 278‐298 K is limited due to ammonia contamination issues Modeled and measured cluster ion distributions agree, differences are likely due to fragmentation